Assessing Banking Services Knowledge among Respondents in the Kachchh Region: A Comparative Analysis of Taluka Perspective - Mrs. Dhruva Jani (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Banking is the backbone of the economy. The main objective of this study is to find out whether the account holders of Abdasa and Nakhatrana in the villeges rural area of Kutch district use various services offered by the banks. The purposive sampling method is Use for Sample. The data of the study was collected from primary and secondary sources. A total of 80 respondents have been selected from these 10 villages of Abdasa and Nakhatrana Talukas of Kachchh District. It was found that the various banking services such as issuing drafts, pension payments, grating loans, the level of service knowledge of the bank have been found to be lower among the people of Nakhatrana taluka compared to Abdasa taluka